2021
DOI: 10.3390/ijerph19010350
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress in Men during the COVID-19 Pandemic in Brazil: The Role of the Sociodemographic Variables, Uncertainty, and Social Support

Abstract: Objective: To analyze the relationships between sociodemographic variables, intolerance to uncertainty (INT), social support, and psychological distress (i.e., indicators of Common Mental Disorders (CMDs) and perceived stress (PS)) in Brazilian men during the COVID-19 pandemic. Methods: A cross-sectional study with national coverage, of the web survey type, and conducted with 1006 Brazilian men during the period of social circulation restriction imposed by the health authorities in Brazil for suppression of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 77 publications
0
16
0
4
Order By: Relevance
“…The discursive findings are permeated by contradictions, which express the discomfort of men when confronted with tensions to hegemonic patterns of masculinity, driven by the cataclysmic effects caused by the pandemic ( Guan et al, 2020 ; Sousa et al, 2022 ). The loss of structurally attributed social roles has had significant repercussions on daily routine, the maintenance of status, the performance of tasks and functions, and the way of being and being in the world during a pandemic ( Freitas et al, 2020 ; Lancet, 2020 ; Nicola et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The discursive findings are permeated by contradictions, which express the discomfort of men when confronted with tensions to hegemonic patterns of masculinity, driven by the cataclysmic effects caused by the pandemic ( Guan et al, 2020 ; Sousa et al, 2022 ). The loss of structurally attributed social roles has had significant repercussions on daily routine, the maintenance of status, the performance of tasks and functions, and the way of being and being in the world during a pandemic ( Freitas et al, 2020 ; Lancet, 2020 ; Nicola et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has shown that the COVID-19 outbreak had a significant psychological impact on pregnant women (14)(15)(16). Temporary closure of public places, strict quarantine policies, and other measures were taken in various countries to prevent the spread of the virus (14,(17)(18)(19). There was a lot of available negative news information about COVID-19 online, which may increase distress and fears for the users.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, due to the severity of COVID-19 infections, in 2020 the adoption of some non-pharmacological measures of individual scope began, such as frequent hand washing with soap and water, use of 70% alcohol, use of masks and social distancing, the latter in order to avoid places with large agglomerations, reducing the risk of exposure [ 2 ]. This health crisis generated negative problems in the mental health of the world population [ 3 ], such as anxiety problems in health professionals (36%), university students (34.7%), general population (34%), teachers (27.2%), parents (23.3%), pregnant women (19.5%) and police (8.79%) [ 4 ]. In addition, children were also affected, especially by the unprecedented change in routines and behaviors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%